Explanation strategies as an empirical-analytical lens for socio-technical contextualization of machine learning interpretability - Jesse Josua Benjamin and Christoph Kinkeldey and Claudia Müller-Birn and Tim Korjakow and Eva-Maria Herbst (Proceedings of the ACM on human-computer interaction, 2022)
During a research project in which we developed a machine learning (ML) driven visualization system for non-ML experts, we reflected on interpretability research in ML, computer-supported collaborative work and human-computer interaction. We found that while there are manifold technical approaches, these often focus on ML experts and are evaluated in decontextualized empirical studies. We hypothesized that participatory design research may support the understanding of stakeholders' situated sense-making in our project, yet, found guidance regarding ML interpretability inexhaustive. Building on philosophy of technology, we formulated explanation strategies as an empirical-analytical lens explicating how technical explanations mediate the contextual preferences concerning people's interpretations. In this paper, we contribute a report of our proof-of-concept use of explanation strategies to analyze a co-design workshop with non-ML experts, methodological implications for participatory design research, design implications for explanations for non-ML experts and suggest further investigation of technological mediation theories in the ML interpretability space.
Keywords: explainable machine learning; explanation strategies; participatory design; post-phenomenology; subject-matter experts; Human-Computer Interaction; Artificial Intelligence; Computers and Society; Computer Science